2013
DOI: 10.1103/physrevb.87.085128
|View full text |Cite
|
Sign up to set email alerts
|

Hard x-ray photoemission and density functional theory study of the internal electric field in SrTiO3/LaAlO3oxide heterostructures

Abstract: Hard x-ray photoemission and density functional theory study of the internal electric field in SrTiO3/LaAlO3 oxide heterostructures Slooten, E.; Zhong, Z.; Molegraaf, H.J.A.; Eerkes, P.D.; de Jong, S.; Massee, F.; van Heumen, E.; Kruize, M.K.; Wenderich, S.; Kleibeuker, J.E.; Gorgoi, M.; Hilgenkamp, H.; Brinkman, A.; Huijben, M; Rijnders, G.; Blank, D.H.A.; Koster, G.; Kelly, P.J.; Golden, M.S. Published in:Physical Review B DOI:10.1103/PhysRevB.87.085128 Link to publicationCitation for published version (APA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 41 publications
(76 reference statements)
7
66
2
Order By: Relevance
“…These results show that photon intensity reduction by three orders of magnitude does not lead to a detectable restoration of the internal LAO band bending nor to a notable decrease of charge carriers at the interface. In agreement with the conclusions of another recent HAXPES study, 22 our findings therefore seem to indicate that the effect of photogenerated carriers on band bending is small. However, already the weakest intensities used may be too close to saturation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results show that photon intensity reduction by three orders of magnitude does not lead to a detectable restoration of the internal LAO band bending nor to a notable decrease of charge carriers at the interface. In agreement with the conclusions of another recent HAXPES study, 22 our findings therefore seem to indicate that the effect of photogenerated carriers on band bending is small. However, already the weakest intensities used may be too close to saturation.…”
Section: Discussionsupporting
confidence: 93%
“…An alternative explanation for the apparent flat band situation has been provided by recent theoretical studies which allow for the presence of oxygen vacancies in the LAO film 22,26,[39][40][41] (not to be confused with the role of vacancies in the STO substrate). In these calculations, it is found that the cost of energy associated with the generation of these defects, i.e., their enthalpy of formation, assumes a minimum at the LAO surface and that each (positively charged) oxygen vacancy leaves two electrons which are transferred to the interface.…”
Section: Discussionmentioning
confidence: 99%
“…34 This hypothesis, if confirmed, could be consistent with the observation that BE shifts of electrostatic nature are hardly found in LaAlO 3 /SrTiO 3 . 30,[36][37][38] At the end we address the general importance of the observed Sr-segregation for the physics of the oxide heterostructures. Any attempt to directly link this phenomenon to interface conductivity would be highly speculative at this stage.…”
mentioning
confidence: 99%
“…The electronic reconstruction scenario, however, was also seriously cast into doubt by X-ray photoemission measurements providing a fairly sensitive probe for binding energy shifts -e.g., due to an internal electric field in the LaAlO 3 film -but being unable to reveal such traces of a finite potential gradient in the data [83][84][85]. Likewise, angle-resolved photoemission measurements using soft X-rays failed to observe O 2p-derived hole pockets due to the LaAlO 3 valence band Fermi level crossing as expected and predicted in an electronic reconstruction scenario [86].…”
Section: Generic and Specific Doping Mechanismsmentioning
confidence: 63%